AHP기법을 활용한 교량 상부구조의 VE검토 - 이광균 (The Graduate School, Ajou University, 2007)
In the design of infrastructure such as bridge, engineers need to take many factors and details into consideration. Safety and serviceability of the structure that satisfy all design regulations are the most important and social functions and aesthetics should be considered likewise in the design of bridge. the purpose of this study is to select a best alternative plane of presented superstructure types (steel box girder, plate girder, PSC-I girder) in the planning stage of bridge construction project. The study has been performed using the Analytic Hierarchy Process (AHP) technique and Life Cycle Cost (LCC) optimization. Multi-attribute decision process of a bridge superstructure is systematically suggested by attribute evaluation using AHP method. Economic attribute of many features is evaluated in particular by LCC optimization. Relative weight among alternatives and attributes is evaluated by using AHP method. In this AHP method, the evaluation items are economic, landscape, constructability, maintenance, stability and functionality of a bridge superstructure. When AHP method has been performed, pair-wise comparisons Matrix evaluate for security of consistency. VE based on AHP method is performed independently for three road types. These road types are national expressway, national highway and provincial road.
학위논문(석사)--아주대학교 일반대학원 :건설교통공학과,2007.2
Keywords: AHP Method; LCC 최적설계